Historical traces in Southern Grevena during Ottoman occupation - Vasileios D. Spanos (Historijski pogledi)
The main body of the work is related to the succinct presentation of the historical course of each settlement in the southern part of the Prefecture of Grevena, during the Turkish rule in Greece. The originality of the subject lies in the use of mainly primary literature and the study of the specific area was decided for practical reasons. The specific area is close to the monastic center of Meteora but also to other monasteries, as a result of which there is an abundance of literature sources that can derive from these monasteries. Also, the area was part of the itineraries followed by many foreign travelers, who from Ioannina were heading either to Thessaloniki and Constantinople or to Southern Greece. These reasons, combined with the fact that it would be difficult, if not impossible, to study all the Thessalian settlements and end up to safe conclusions, given the small number of sources for the rest of the Thessalian area, led to this choice. Regarding the chronological limits, the research moved over a period spanning from the 14th century to the 19th century and the beginning of the 20th since the conquest of Thessaly by the Ottomans began at the end of the 14th century and a part of it (today's southern part of the Prefecture of Grevena and the area of Elassona), was liberated in 1912. Consequently, the southern part of the Prefecture of Grevena and the territory of today’s Prefecture of Trikala, constituted then, the area of northwest Thessaly which already from the era of Byzantium was a single geographical entity. Regarding the content of each settlement, the time of its creation (or the first reference to the sources) and dissolution (if it does not exist today) of the settlements, the presentation of population data and data on ownership status, information on the economic and social life (functioning of schools, notable events, monuments of a mainly ecclesiastical nature) and anything else deemed worthy of mention were taken into account. In particular, attention was paid to the detection of all reports of the settlement, in written sources (published and unpublished), so that all the information concerning each settlement, even the simple reports, become known and accessible to the research and also in order to record all types with which each toponym is found, which also facilitates its etymology (although this identification was not always possible). To gather all this material, extensive research was carried out in all kinds of unpublished or published sources (ledgers - texts of Thessalian monasteries - publications of the time - texts of travelers - texts of geographers (Greek and foreign) - collections of sources and documents). Two censuses, the one of 1454/55 carried out by the Ottomans and the one of 1881 carried out by the Greek Ministry of the Interior after the integration of Thessaly into the Greek kingdom (except for the areas of Deskati and Elassona), were the main axes. The research was necessarily extended to sources from the Byzantine era in order to determine how many of the identified settlements existed during this era.